KOMPOSISI DAN SEBARAN TUMBUHAN BERKHASIAT OBAT BERDASARKAN TINGKATAN VEGETASI DI HUTAN KERANGAS KABUPATEN BARITO SELATAN - Heni Nopita Sari; Kissinger Kissinger; Gusti Syeransyah Rudy (Universitas Lambung Mangkurat, 2020)
Kerangas forest as a forest area with special character is suspected to have potency of medicinal plants. The objectives of this research are i) to obtain vegetation composition in the forest, ii) describe the distribution of medicinal plants based on vegetations levels, iii) identifying medicinal plants species based on local knowledge. The method used is the prited path by way of Purposive Sampling and semi structured interview method. The location of the research is categorized into 2 criteria, namely old secondary forest and young secondary forest. The result showed that the composition of species found were 18 species of vegetation in young secondary forest and 32 types of vegetation in old secondary forest. The highest distribution of medicinal plants in young secondary forest is found at the pole level of 40%. The highest distribution in the old secondary forest is found at the tree level of 20,83%. Identified research location there are 20 species, 10 of which have been used by society as material for treatment. The distribution of medicinal plants in old secondary forest more than the young secondary forest. Keywords: Composition, Potency, Distribution, Medicinal Plants